The LEGO movie 2 : junior novel - Meredith Rusu (New York, NY : Scholastic Inc., 2019)
With the city in ruins after the DUPLO alien attack, Emmet must save his friends when they are taken by a mysterious helmeted figure and flown ino space.
Keywords: LEGO toys -- Fiction; Adventure and adventurers -- Fiction